Practices for Implementation of the Critical Success Factors in Software Outsourcing Partnership from Vendors’ Perspective: A Literature Review: Practices for implementation of the Critical Success Factors in Software - Ali, Sikandar; Khan, Siffat Ullah (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Software outsourcing partnership (SOP) is a trustful relationship between client and vendor organizations for shared goals. A SOP is different to ordinary software development outsourcing relationship. Usually a successful outsourcing relationship may lead to SOP. Software companies currently use a wide variety of mechanisms to outsource software development work. Beside all, SOP is an emerging strategy. The development of SOP depends on the proper implementation of various critical success factors (CSFs) like ‘mutual trust’, ‘effective and timely communication’, ‘mutual interdependence and shared values’, ‘organisational proximity’, ‘quality production’ and ‘3C (coordination, cooperation and collaboration)’. Moreover, the practices of SOP in the software industry are very little. The objective of this research is to identify practices for implementing CSFs in SOP. We have identified a list of 142 ‘practices’ for various CSFs through SLR methods. Initially we have found 375 research articles through SLR process and finally 65 papers were selected. In total 142, practices identified through SLR for 14 CSFs.